CCNP Security VPN 642-648 official cert guide - Hooper, Howard (Cisco Press, 2012)
The official study guide helps you master all the topics on the CCNP Security VPN exam, including Configuring policies, inheritance, and attributes · AnyConnect Remote Access VPN solutions · AAA and Dynamic Access Policies (DAP) · High availability and performance · Clientless VPN solutions · SSL VPN with Cisco Secure Desktop · Easy VPN solutions · IPsec VPN clients and site-to-site VPNs The CD-ROM contains a free, complete practice exam. Includes Exclusive Offer for 70% Off Premium Edition eBook and Practice Test Pearson IT Certification Practice Test minimum system requirements: Windows XP (SP3), Windows Vista (SP2), or Windows 7; Microsoft .NET Framework 4.0 Client; Pentium class 1GHz processor (or equivalent); 512 MB RAM; 650 MB disc space plus 50 MB for each downloaded practice exam This volume is part of the Official Cert Guide Series from Cisco Press. Books in this series provide officially developed exam preparation materials that offer assessment, review, and practice to help Cisco Career Certification candidates identify weaknesses, concentrate their study efforts, and enhance their confidence as exam day nears. CCNP Security VPN 642-648 Official Cert Guide is a best of breed Cisco exam study guide that focuses specifically on the objectives for the CCNP Security VPN exam. Cisco Certified Internetwork Expert (CCIE) Howard Hooper shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. CCNP Security VPN 642-648 Official Cert Guide presents you with an organized test-preparation routine through the use of proven series elements and techniques. "Do I Know This Already?" quizzes open each chapter and enable you to decide how much time you need to spend on each section. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. The companion CD-ROM contains a powerful testing engine that enables you to focus on individual topic areas or take a complete, timed exam. The assessment engine also tracks your performance and provides feedback on a module-by-module basis, laying out a complete assessment of your knowledge to help you focus your study where it is needed most. Well-regarded for its level of detail ...
Print version record
Keywords: Electronic data processing personnel -- Study guides -- Certification; Computer networks -- Study guides -- Security measures -- Examinations; Extranets (Computer networks) -- Study guides -- Security measures -- Examinations; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Extranets; Sécurité; Mesures; Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Electronic data processing personnel; Certification; examination study guides; Study guides; Guides de l'étudiant